ANALISIS PENGARUH PRODUK DOMESTIK BRUTO DAN SUKU BUNGA TERHADAP FOREIGN DIRECT INVESTMENT DI INDONESIA TAHUN 1997 - 2016 - Novinta Nurmasari; Zainal Arifin (Jurnal Ilmu Ekonomi JIE, 2018)
This research aimed to analyze the effect of Gross Domestic Product (GDP) and interest rates on Foreign Direct Investment (FDI). The data used in this research is time series data and the method used is Error Correction Model (ECM). This research is quantitative descriptive that depict the influence of Gross Domestic Product (GDP) and Interest Rate to Foreign Direct Investment in Indonesia in 1997 - 2016. Based on analysis findings, all variables used by stasionary in first difference, the dependent and independent variables in the cointegration equation have a long-term relationship. In the long term gross domestic product and interest rates have a positive and significant influence on Foreign Direct Investment while in the short term gross domestic product has no significant effect on FDI. The different from FDI, interest rates in the short term have a positive and significant effect on FDI.Keywords : Error Correction Model, Foreign Direct Investment, Gross Domestic Product, Interest Rate